Photo-affinity labelling at the peptidyl transferase centre reveals two different positions for the A- and P-sites in domain V of 23S rRNA. - Steiner, G (1988)
Photo-reactive 3-(4'-benzoylphenyl)propionyl-Phe-tRNA bound to the A- or the P-site was crosslinked to 23S RNA upon irradiation at 320 nm. The sites of reaction were identified as U-2584 and U-2585 at the A-site and A-2451 and C-2452 at the P-site. Minor crosslinks from both sites were observed at nucleotides A-2503 to U-2506. All sites identified lie in close proximity according to the secondary structure model and constitute part of the highly conserved loop region of domain V. Antibiotics known to inhibit peptidyl transferase activity had a pronounced effect on photo-crosslinking. In addition, tetracycline was also shown to photo-crosslink to this region. These experiments permit a dissection of the peptidyl transferase region on the 23S RNA into two distinct areas for the A- and P-site.